Differentiation of Salmonella strains from the SARA, SARB and SARC reference collections by using three genes PCR-RFLP and the 2100 Agilent Bioanalyzer - Soler-García, Ángel A.; De Jesús, Antonio J.; Taylor, Kishana; Brown, Eric W. (Frontiers in Microbiology, 2014)
Rapid molecular typing methods are important tools in surveillance and outbreak investigations of human Salmonella infections. Here we described the development of a three-genes PCR-RFLP typing method for the differentiation of Salmonella species, subspecies and serovars using the Agilent 2100 Bioanalyzer. The fliC, gnd and mutS genes were PCR-amplified in 160 Salmonella strains representing the two Salmonella species, six subspecies and 41 different serovars of S. enterica subspecies enterica. PCR products were individually cut with two different restriction enzymes and the resulting 930 restriction patterns were collected using the Agilent 2100 Bioanalyzer followed by cluster analysis. Both species of Salmonella were differentiated by conventional PCR. All of S. bongori tested were gnd PCR negative due to a mismatch at the 3’-end in one the PCR primers. Salmonella subspecies were differentiated into third-teen homogeneous groups representing each of the six subspecies by cluster analysis of restriction patterns generated from the mutS gene cut with AciI. S. enterica subspecies enterica serovars were further differentiated by the combination of the three target genes and five out the six sets of restriction patterns with a discriminatory power of 0.9725 by cluster analysis. The combined RFLP results of five sets of restriction patterns allowed us to assign each of the 160 strains to one of 128 restriction types. During inoculation studies we were able to identify S. Saintpaul and Typhimurium from 24 hour pre-enrichment samples using the described method. The use of fliC, gnd and mutS PCR-RFLP with the Agilent 2100 Bioanalyzer can provide an accessible and automated alternative method for differentiation of Salmonella pathogens.